Characteristics of multi drug resistant tuberculosis cases at a selected tertiary level hospital - Mahbubul Hoque; Mahfuzar Rahman; S.M.M. Saleh Bhuiyan; Mahbubur Rahman (International Journal of Medical Research and Review, 2017)
Background: This study was carried out to determine the characteristics of MDR-TB cases under treatment at National Institute of Diseases of the Chest and Hospital (NIDCH), Mohakhali, Dhaka.Methods: This was a descriptive cross sectional study among 442 diagnosed MDR-TB patients admitted in NIDCH of which 303 MDR-TB patients were included as respondents. The respondents were selected purposively and they were interviewed with duly pre-tested research instruments.Results: Among the study populations (303), all were resistant to H & R and 149 (57.7%) consumed standard drugs regimen contained H, R, E & S. In addition the factors related to develop MDR-TB mostly as non-compliance, overcrowding and exposure to MDR-TB were 190 (73.7%), 261 (86.1%) and 81 (26,7%) respectively. In this study, time interval between completed anti-TB treatment and diagnosis of MDR-TB found 01 to 06 years among 55.4% respondents. Moreover tools used for diagnosis of MDR-TB were found in 258 (85.1%) as smear for AFB, Gene expert tests and Culture. Age group 16 to 30 yrs 184 (60.7%), income group 10001 to 20000 taka per month 143 (47.2%), educational qualification class VI-X 72 (23.8%) and urban population 180 (59.4%) were affected more. The association between type of house, crowding status and occurrence of MDR-TB were found statistically significant (p<0.05) but source of drugs, compliance of treatment, availability of drugs and occurrence of MDR-TB shown statistically highly significant, (p<.001). Correlation with age, family income and time gap of diagnosis MDR-TB was statistically significant (p<0.05). Principal.Conclusion: Study findings demands establishment of standard diagnostics procedures/laboratories at all secondary and tertiary care hospitals and TB clinics in the country in support of uniformity of intervention therapy.